Ray watching: the highly protected, British prison experience of Martin Luther King’s killer - Ling, Peter (Taylor & Francis, 2017)
The arrest of James Earl Ray at London Airport on 8 June 1968 marked the final stage of an international manhunt that had begun with the murder of Martin Luther King Jr. on 4 April. Arrested for travelling on a false passport and with an unlicensed firearm, Ray faced extradition to the US to face charges of murder. While in prison in Britain, the US Government feared that he might escape, commit suicide or be himself assassinated. Each of these outcomes risked reigniting the African-American anger that had wracked major US cities in April. Accordingly the UK Government was requested to take special security measures and complied. Was this a supine response from a Labour government anxious to placate a disgruntled superpower ally or did it also reflect contemporaneous UK anxieties about the tense state of race relations at home? Drawing on Home Office records, this article examines these questions.